"Medicine is a tool to allow me to do more interesting things". (19th April 2010) - Gulland, Anne
Abstract : With ambitious plans to introduce rotavirus vaccine into 44 countries, the Global Alliance for Vaccines and Immunisation is now seeking new donors from east Asia. Anne Gulland reports